Comprehensive Dental Care: Definition and Teaching Tips - Buranachad, Naiyana; Supa-amonkul, Sirirak; Champirat, Tharee; Manopatanakul, Somchai (Khon Kaen University Dental Journal, 2021)
The aim of this literatures review is to assemble the mainstream educational theories and contemplative pedagogy to explain the concept of comprehensive dental care. Technique to develop comprehensive mind in dental students was also included. Humanistic coaching with heuristic approach or simply “teaching with compassionate communication” is the key to this success. The first move to this path is “deep listening”. With this easy step, teachers are all invited to become a dental educational developer or ingenuously dental educational coach or facilitator. To patronize dental students and patients, policy makers are key persons to transform this little step into a great leap of Thai dental education.